2021
DOI: 10.3390/md19010030
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Structure and Its Impact on Glucose Metabolism: Implications for Diabetes and Cancer Therapy

Abstract: Fucoidans are complex polysaccharides derived from brown seaweeds which consist of considerable proportions of L-fucose and other monosaccharides, and sulphated ester residues. The search for novel and natural bioproduct drugs (due to toxicity issues associated with chemotherapeutics) has led to the extensive study of fucoidan due to reports of it having several bioactive characteristics. Among other fucoidan bioactivities, antidiabetic and anticancer properties have received the most research attention in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 112 publications
0
23
0
Order By: Relevance
“…Sulfated polysaccharides isolated from seaweeds have been reported to possess various bioactivities [ 12 , 13 , 14 , 15 , 16 , 17 ]. In particular, seaweed-derived sulfated polysaccharides possess potent immunostimulatory and anti-inflammatory effects [ 12 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sulfated polysaccharides isolated from seaweeds have been reported to possess various bioactivities [ 12 , 13 , 14 , 15 , 16 , 17 ]. In particular, seaweed-derived sulfated polysaccharides possess potent immunostimulatory and anti-inflammatory effects [ 12 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, fucoidan is a popular nutraceutical in Japan and other nations due to their health-enhancing potential [201]. The relevance of fucoidan in preventing diabetes in some animal studies has been highlighted [108,202]. Shan et al [203] reported the ability of F. vesiculosus fucoidan to inhibit α-glucosidase in vitro and to decrease the fasting blood glucose and HbA1c levels of db/db mice.…”
Section: Glucose Homeostasismentioning
confidence: 99%
“…It has also been reported that fucoidan provides antidiabetic action by inhibiting α-amylase and α-glucosidase. Moreover, the antidiabetic property of fucoidan is attributed to activate the PI3K/PKB pathway, which regulates insulin production and stimulates GLUT4 translocation [91]. Implications of fucoidan have also been identified in healing inflammation via inhibition of NO production, downregulation of iNOS, COX-2, IL-1 β, TNF-α, NF-κB expression, and regulation of ERK, JNK, MAPK, and Akt pathways [88,90].…”
Section: Polysaccharides Fucoidanmentioning
confidence: 99%